Associations between inattention and impulsivity ADHD symptoms and disordered eating risk in a community sample of young adults. Issue 13 (4th October 2022) - Martin, E.; Dourish, C. T.; Hook, R.; Chamberlain, S. R.; Higgs, S.
Abstract: Background: Symptoms of attention deficit hyperactivity disorder (ADHD) and trait impulsivity have been associated with disordered eating but are seldom assessed in community studies, or longitudinally and little is known about the mediating mechanisms. Methods: We tested associations between ADHD symptoms and disordered eating cross-sectionally and between trait impulsivity and disordered eating longitudinally. We utilised data from a normative cohort of young adults (642 participants: 65% female, M age = 23 years). Participants were classified as high risk or low risk for disordered eating using the SCOFF instrument. In the first two steps of both cross-sectional and longitudinal hierarchical logistic regression models, demographics and covariates were entered. For the cross-sectional regression, Adult ADHD self-report scale (ASRS) scores, separated into inattentive and hyperactive/impulsive symptoms, were entered in the third step. In a separate longitudinal model, Barratt impulsivity scale subscales (attentional, motor and non-planning impulsivity) were entered in the third step. Depression, as assessed by the moods and feelings questionnaire (MFQ), was examined as a mediator. Results: Cross-sectionally, sex, MFQ score and inattentive symptoms predicted disordered eating risk (model R 2 = 20%). Longitudinally, sex, MFQ score and attentional impulsivity predicted disordered eating risk (model R 2 = 16%). The relationship between inattentive symptoms and the disordered eating risk was partially mediated by MFQ score, whereas the relationship between attentional impulsivity and the disordered eating risk was fully mediated by MFQ scores. Conclusions: These data highlight (1) a specific role for inattentive symptoms of ADHD and (2) the importance of both depression and impulsivity in predicting eating disorder risk.